Good Corporate Governance Analysis to the Profitability of PT. Telekomunikasi Indonesia Tbk. - Rida Julian Ardea; Nazma Azizah; Riza Nurrizkinita Zein (Nusantara Science and Technology Proceedings, 2020)
This study aims to examine the effect of liquidity and good corporate governance on profitability in the company. as well as to find out how the effect of Good Corporate Governance (GCG) on company profitability, measured by Return on Equity (ROE), Return on Assets (ROA), and return on capital and self-employed (ROCE). This research was conducted at PT. Telkom Telekomunikasi Indonesia Tbk. listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This sample selection is done by the data analysis method. The results of this study indicate that Good Corporate Governance (GCG) has a significant effect on firm value. Good Corporate Governance (GCG) has no significant effect on profitability with the proxy of Return on Assets (ROA). and with this method can find out the liquidity of financial statements in the company PT. Indonesian communication.